2004
DOI: 10.1097/01.ccm.0000139950.39972.68
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous breathing through an inspiratory impedance threshold device augments cardiac index and stroke volume index in a pediatric porcine model of hemorrhagic hypovolemia

Abstract: ITD-assisted breathing significantly augmented systolic blood pressure, cardiac index, and stroke volume index in this pediatric porcine model of hemorrhagic hypovolemia. These effects appear related to increased left ventricular preload and not by increased systemic vascular resistance or heart rate. These beneficial effects of ITD-assisted breathing are not changed by the addition of positive end-expiratory pressures of 3 cm H2O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 20 publications
4
35
0
1
Order By: Relevance
“…The ITD-7, compared to a placebo sham, has been shown to increase stroke volume and to maintain blood pressure in normal volunteers subjected to acute orthostatic stress, and also to enhance cerebral blood flow in patients with hypotension due to lowerbody negative pressure (11,18). Use of the ITD-7 in animal and human studies results in an immediate increase in cardiac stroke volume, systolic blood pressure, diastolic pressure, and improved vital organ perfusion pressures (4,13,(15)(16)(17). More recently, the ITD-7 has been shown to maintain perfusion pressures in the setting of severe hypotension associated with application of lower-body negative pressure in normal volunteers (14,19).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The ITD-7, compared to a placebo sham, has been shown to increase stroke volume and to maintain blood pressure in normal volunteers subjected to acute orthostatic stress, and also to enhance cerebral blood flow in patients with hypotension due to lowerbody negative pressure (11,18). Use of the ITD-7 in animal and human studies results in an immediate increase in cardiac stroke volume, systolic blood pressure, diastolic pressure, and improved vital organ perfusion pressures (4,13,(15)(16)(17). More recently, the ITD-7 has been shown to maintain perfusion pressures in the setting of severe hypotension associated with application of lower-body negative pressure in normal volunteers (14,19).…”
Section: Discussionmentioning
confidence: 95%
“…Whereas previous studies have demonstrated that the ITD-7 can be used in severely hypotensive animals and in relatively hypotensive or hypovolemic patients, this is the first application of the ITD-7 in patients presenting to the ED and prehospital setting in need of immediate therapy for hypotension (4,8,(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Generation of negative intrathoracic pressure by indirectly increasing inspiratory effort (20) or by applying direct airway vacuum (11) between positive pressure ventilations resulted in a remarkable decrease in ICP by a direct transfer of pressure and increasing venous drainage, as it can be seen by the immediate pressure changes of the ICP correlating with the changes in airway pressures. The effect seems to be mediated by a mechanical process through the venous channels of the paraspinal plexuses and the increase of venous return by the jugular veins.…”
Section: Discussionmentioning
confidence: 95%
“…13 Animal studies had previously demonstrated that an ITD increased mean arterial pressure in heat stroke, 23 and blood pressure, 24 cardiac output, 25 and survival time 26 after hypotension induced by severe blood loss. To determine if there were similar effects in humans, healthy subjects were exposed to progressive lower-body negative pressure.…”
Section: Patient Tolerance and Response To Acute Central Hypovolemia mentioning
confidence: 99%